Enhancing the effectiveness of tobacco package warning labels: a social psychological perspective. Issue 3 (1st September 2002) - Strahan, E J; White, K; Fong, G T; Fabrigar, L R; Zanna, M P; Cameron, R
Abstract : Objective: To outline social psychological principles that could influence the psychosocial and behavioural effects of tobacco warning labels, and to inform the development of more effective tobacco warning labels. Data sources: PsycInfo and Medline literature searches and expert guided selection of principles and theories in social psychology and of tobacco warning labels, including articles, books, and reports. Conclusions: Tobacco warning labels represent a potentially effective method of influencing attitudes and behaviours. This review describes social psychological principles that could be used to guide the creation of more effective warning labels. The potential value of incorporating warning labels into a broader public health education campaign is discussed, and directions for future research are suggested.